Autoimmune antibodies in first-episode psychosis with red flags: A hospital-based case-control study protocol - Wang, Jianjun; Liu, Xuan; Lian, Jie; Zheng, Haotao; Cai, Dongbin; Cai, Haobin; Zhou, Dan; Lin, Songjun; Kong, Fanxin; Qin, Xiude; Bi, Jianqiang (Frontiers in Psychiatry, 2022)
Background: Research is increasingly identifying an overlap between psychosis and immunological dysregulation. Certain autoantibodies are being identified in a small but probably relevant subgroup of patients with psychosis. The term “autoimmune psychosis” (AIP) and its corresponding red-flag signs present the opportunity for a new field in psychiatry to promote diagnostic workup and immunomodulating therapy in individual cases. Objectives: The present protocol aims to determine the seroprevalence of autoantibodies in first-episode psychosis (FEPs) using AIP red flag signs, and to explore the frequency of autoantibody subtypes and potential mediating confounders. Methods/Design: This is a hospital-based case-control study. All participants will be consecutively selected from the main tertiary psychiatric hospital in Shenzhen City, China. Individuals admitted to the psychiatric ward and diagnosed with FEPs will be enrolled. Based on recent consensus, participants with red flags of AIPs will be defined as cases, while the remainder will be matched as controls. Seropositive antibodies will be detected and verified in cerebrospinal fluid (CSF) samples based on the fixed cell - based assay (CBA) method. The propensity score-adjusted odds ratios will be determined to investigate the key mediating confounders regarding autoantibody subtypes and red flag subsets. Discussion: The results of this study will facilitate the early identification of AIPs in FEP patients using the red flag sign and help identify key mediators that improve the accuracy of diagnostic algorithms. It will have clinical significance to focus on serum antibodies that have been verified in CSF samples, due to its consistency with clinical practices in current psychiatry.